A Preliminary Study on the Relationship between Death Anxiety, Spiritual Well-being and the Meaning of Life among Individuals Living in Klang Valley, Malaysia - Hoesni, Suzana Mohd (International Journal of Psychosocial Rehabilitation, 2020)
To investigate the relationship between death anxiety, spiritual well-being and the meaning of life among individuals from critically developed areas in Klang Valley, Malaysia. This is an exploratory research study. The study involved 309 participants who were selected using the cluster sampling method from 10 of the most critically developed locations in Klang Valley, Malaysia. Questionnaires were distributed to respondents who had stated their agreement to the informed consent. The questionnaires consisted of questions regarding personal background, death anxiety, spiritual well-being and the meaning of life. Completed questionnaires were then collected and analyzed. The results show that there is a small, negative and significant relationship between the dimensions of death anxiety (extinction) and spiritual well-being (existential) (rs=- 0.12**, p<0.01). Conversely, there is a small, positive and significant relationship between death anxiety (cessation) (rs=.27**, p<0.01) and death anxiety (extinction) (rs =.18**, p<0.01) with meaning of life (searching).Results also show that there is a small, positive and significant relationship between death anxiety (cessation) and spiritual well-being (religious) (rs=0.15**).Findings indicate that individuals with more understanding on existential aspects within the dimension of spiritual well-being are prone to lesser death anxiety experience. In addition, individuals who achieved the meaning in life have lower scores in death anxiety. Implications of this study towards helping professionals such as counselors, therapists and social workers working with individuals facing death anxiety. Future research suggestions relating to death anxiety were also discussed.